Physical Stability Evaluation of 5% Curcuma Longa Extract Using the Maceration Extraction Method - Azhar Arrosyid; Nurrachmat Mulianto; Nugrohoaji Dharmawan (International Journal Labs, 2025)
Curcuma longa (turmeric) is a medicinal plant widely used for its anti-inflammatory, antioxidant, and antimicrobial properties. Cream formulations are ideal for topical delivery due to their ease of application, good absorption, and patient acceptability. The maceration method is a simple and cost-effective technique for obtaining plant extracts without compromising bioactive compounds. This study aimed to evaluate the physical stability of a cream formulation containing 5% Curcuma longa extract prepared using the maceration extraction method. The extract was prepared through maceration of dried turmeric rhizome using ethanol, followed by evaporation to obtain the concentrated extract. The cream was formulated with stearic acid, cera alba, vaselin album, triethanolamine, propylene glycol, and distilled water as base components. Physical stability parameters were tested over seven days, including pH, dispersion, and adhesion tests. Statistical analysis was performed using the Friedman test. The pH values ranged from 7.33 to 7.50 (p = 0.006), indicating mild alkalinity but remaining within an acceptable range for topical application. Dispersion remained stable throughout the observation period (p = 0.452), while adhesion increased significantly from 182.71 to 200.04 seconds (p = 0.006), suggesting improved cohesiveness. The 5% Curcuma longa extract cream demonstrated good physical stability, indicating that the maceration method is a viable approach for developing stable topical herbal formulations.